3.113. Rozwiąż równanie: a) 2x ^ 2 + 5x – 12 = 0 d) 2(x ^ 2 + 4) = – 3x b) 4x ^ 2 – 7x = 0 e) 3x ^ 2 – 6 = 0 b) 1 – 4x ^ 2 = 0 e) 2 * (x + 1) ^ 2 = 18 b) 3x ^ 2 – 7x = 20 e) 49x ^ 2 = 4x c) 3x ^ 2 + 8 = 0 f) (x+: )(x – 7 ()=0; 1/2 * (x ^ 2 + 2) = 7 f) (x – 13) ^ 2 + 1 = 0 c) 9x ^ 2 = 12x – 4 f) 16x ^ 2 + 25 = 40x

3.113. Rozwiąż równanie: a) 2x ^ 2 + 5x – 12 = 0 d) 2(x ^ 2 + 4) = – 3x b) 4x ^ 2 – 7x = 0 e) 3x ^ 2 – 6 = 0 b) 1 – 4x ^ 2 = 0 e) 2 * (x + 1) ^ 2 = 18 b) 3x ^ 2 – 7x = 20 e) 49x ^ 2 = 4x c) 3x ^ 2 + 8 = 0 f) (x+: )(x – 7 ()=0; 1/2 * (x ^ 2 + 2) = 7 f) (x – 13) ^ 2 + 1 = 0 c) 9x ^ 2 = 12x – 4 f) 16x ^ 2 + 25 = 40x